PENGARUH RASIO KECUKUPAN MODAL, LIKUIDITAS BANK, RISIKO KREDIT DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS BANK KONVENSIONAL YANG TERDAF1TAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2016 - Senia Noviani, 14.05.52.0132; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
The purpose of this research are for test and analyze the effect from minimum capital ratio, bank liquidity, credit risk and firm size to commercial bank profitability. In this research use capital adequacy ratio (CAR), loan to deposit ratio (LDR), non performing loan (NPL) and firm size as independent variables and bank profitability that proxied by return on assets (ROA) as dependent variable. The sampling technique is purposive sampling. The sample used was commercial bank that listed on Stock Exchange which published an annual report during 2012-2016. The sample that can be used are 28. The analysis method is double regression. The results are : CAR, LDR and firm size give positive effect and significant on ROA otherwas firm size gives negative effect and not significant on ROA.Keywords : CAR, LDR, NPL, firm size and bank profitability (ROA)